SENTRA PERTANIAN KOTA JAKARTA PUSAT - Fahira Muntaz; J.M. Joko Priyono Santosa (Jurusan Arsitektur dan Perencanaan, 2021)
Climate change is vulnerable to occur in major cities including the city of Jakarta because of the many greenhouse gas emissions resulting from the construction of many buildings and the lack of green land. In addition, the city of Jakarta and major cities in general can not meet their own food needs. Climate change is a very serious threat to the agricultural sector. It is hoped that the city's agricultural center buildings will be able to create architecture for the agricultural sector that is resistant to climate change and accommodate millennial farmers and become examples of agriculture in the future and apply sustainable architecture can be a representation and example of environmentally minded buildings in Jakarta. The design of the city's agricultural center building is located on Kramat Kwitang Highway, Senen Subdistrict, Central Jakarta City, DKI Jakarta. Data analysis is done using theory i.e. analysis based on environmental aspects, building aspects and human aspects. The city's agricultural center building accommodates the main function as a place to cultivate agricultural crops and secondary functions as a means of education and public space. The result that will be achieved is a building that has a basic design concept that competes on sustainable architecture and also biophilic by designing natural elements into vertical buildings. Keywords: Central Jakarta; Farm; Urban Abstrak Perubahan iklim rentan terjadi di kota besar termasuk kota Jakarta karena banyaknya emisi gas rumah kaca yang diakibatkan dari banyak dibangunnya gedung-gedung dan minimnya lahan hijau. Selain itu kota Jakarta dan kota-kota besar pada umumnya tidak dapat mencukupi kebutuhan makanannya sendiri. Perubahan iklim merupakan salah satu ancaman yang sangat serius terhadap sektor pertanian. Diharapkan dengan adanya bangunan sentra pertanian kota ini mampu menciptakan arsitektur untuk sektor pertanian yang tahan terhadap perubahan iklim serta mewadahi petani milenial dan menjadi contoh pertanian di masa depan serta menerapkan arsitektur yang berkelanjutan dapat menjadi representasi dan contoh bangunan berwawasan lingkungan di Jakarta. Perancangan bangunan pusat pertanian kota ini terletak di jalan Raya Kramat Kwitang, Kecamatan Senen, Kota Jakarta Pusat, DKI Jakarta. Analisis data dilakukan dengan menggunakan teori yaitu analisis berdasarkan aspek lingkungan, aspek bangunan dan aspek manusia. Bangunan pusat pertanian kota mewadahi fungsi utama sebagai tempat pembudidayaan tanaman pertanian dan fungsi sekunder sebagai sarana edukasi dan public space. Hasil yang akan dicapai adalah bangunan yang berkonsep dasar rancangan yang berpacu pada sustainable architecture dan juga biophilic dengan merancang unsur alam kedalam bangunan vertikal.